An Investigation of Foreign Language Learners’ Problems in Intercultural Communication - Hamadouche, Mokhtar (Journal of Human Sciences, 2018)
The present paper strives to highlight the relationship between language and culture in communication, in addition to the role religion may play in the activity for some nations, particularly Arab nations and Islam. It investigates specifically the strategies and problems of a sample of Algerian students of English at the University of Oum El Bouaghi while interacting with native speakers through social media.It focuses on the significance of cultural awareness in intercultural communication and attempts to shed light on the reasons behind students’ communication breakdowns. The results show that despite the students’ rather advanced level of English language proficiency, they still find problems in intercultural communication mainly due to cultural differences. Therefore, the integration of a course in cross-cultural communication in language teaching curricula is highly recommended where research in the area should in no way be estranged from the pedagogical practice.